1982
DOI: 10.1093/oxfordjournals.aje.a113417
|View full text |Cite
|
Sign up to set email alerts
|

A Case-Control Study of Cancer of the Endometrium

Abstract: A hospital-based case-control study of the epidemiology of endometrial cancer in women aged 45-74 years was carried out in Connecticut from 1977 to 1979. In total, 167 cases and 903 controls were included. Elevated risks were associated with the following factors: overweight, nulliparity, few pregnancies, use of estrogen replacement therapy, older age at menopause, and a history of ovarian or endometrial cancer in mother or a sister. Whites were more frequently affected than blacks, and better-educated women m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
79
1
2

Year Published

1984
1984
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(93 citation statements)
references
References 0 publications
11
79
1
2
Order By: Relevance
“…In the absence of a previous diagnosis of breast cancer the most consistently reported risk factors for endometrial cancer are nulliparity, late age at menopause, obesity, and oestrogens for menopausal symptoms (Elwood et al, 1977;Ewertz, 1981;Kelsey et al, 1982;La Vecchia et al, 1982;MacMahon, 1974;Salmi, 1979;Wynder et al, 1966). Our results closely agree with those studies.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the absence of a previous diagnosis of breast cancer the most consistently reported risk factors for endometrial cancer are nulliparity, late age at menopause, obesity, and oestrogens for menopausal symptoms (Elwood et al, 1977;Ewertz, 1981;Kelsey et al, 1982;La Vecchia et al, 1982;MacMahon, 1974;Salmi, 1979;Wynder et al, 1966). Our results closely agree with those studies.…”
Section: Discussionsupporting
confidence: 90%
“…This relative risk is also compatible with that obtained for the former study of oestrogen therapy for breast cancer (Hoover et al, 1976). Others (Hulka et al, 1980;Kelsey et al, 1982;Shapiro et al, 1980) have shown that oestrogens must be used for a period of 2-3 years before a significant increase in risk can be detected. Information on doses of oestrogen was well documented for breast cancer therapy, but unfortunately not so for treatment of menopausal symptoms, and a comparison of dosage could not be done.…”
Section: Discussionsupporting
confidence: 86%
“…Because of the possibility of risk of melanoma being related to endogenous hormonal factors, the data was analysed for age at first birth and numbers of livebirths; variables which are important in the aetiology of other hormone related tumours such as breast and ovarian cancer (Brinton et al, 1979;Kelsey et al, 1982;Hildreth et al, 1981). Univariate analysis demonstrated a significant negative association between risk of melanoma and number of live births (Table II), which persisted for superficial spreading melanomas even after adjustment for host factors, educational status and age at first birth.…”
Section: Methodsmentioning
confidence: 99%
“…Table I shows the results of seven studies which have considered the effect of the daily dose of CEE. All except one (Kelsey et al, 1982) found that the risk was greater for doses of 1.25 mg day-1 (and above) than for doses of 0.625mg day-1 (and below), although in two studies this trend was not adjusted for duration of use. Table II shows the effect of the two doses, 0.625 mg and 1.25 mg, of CEE on plasma E2, SHBG and estimated E2 binding.…”
mentioning
confidence: 90%